Eculizumab is efficacious and safe in pediatric patients with various forms of hemolytic uremic syndrome: a retrospective clinical experience of a tertiary center - Lax, Naama; Davidovits, Miriam; Chodick, Gabriel; Bernfeld, Yael; Peled, Orit (Frontiers in Pharmacology, 2025)
BackgroundEculizumab, a terminal complement inhibitor, prevents thrombotic microangiopathy (TMA) and multiorgan damage in hemolytic uremic syndrome (HUS). We evaluated its efficacy and safety in pediatric patients with TMA sub-types: atypical HUS (aHUS), Shiga toxin-producing Escherichia coli (STEC)-HUS, and transplant-associated TMA (TA-TMA).MethodsThis retrospective study included all pediatric patients treated with eculizumab for HUS at Schneider Children’s Medical Center (2011–2020), including those with pre-existing end-stage kidney disease. Clinical and laboratory parameters were analyzed over 28 weeks. The primary endpoint was achievement of complete TMA response, defined by sustained normalization of hematologic parameters and renal function. Secondary endpoints included TMA event-free status and additional clinical improvements.ResultsTwenty-four pediatric patients (median age 5.8 years) were included: 13 with aHUS, 5 with STEC-HUS, and 6 with TA-TMA. A complete TMA response was achieved in 12 (50%) of the patients overall: 7 (54%) with aHUS, 3 (60%) with STEC-HUS, and 2 (33%) with TA-TMA. TMA event-free status was reached in 15 (63%) patients. Significant improvements were observed in platelet count (63%), lactate dehydrogenase levels (76% within the first week), hemoglobin (60%), and estimated glomerular filtration rate (79%); while CH-50 levels decreased. No severe adverse events were attributed to eculizumab. Chronic kidney disease stage improved for 17 (90%).ConclusionThe efficacy and safety of eculizumab for three TMA subtypes in pediatric patients potentially expands its therapeutic applications. The complete TMA response rate in aHUS supports eculizumab as a first-line use, while the response rate in STEC-HUS suggests potential efficacy beyond eculizumab’s primary indication. The early hematologic responses and reduced CH-50 levels confirm the role of eculizumab complement-mediated HUS and underscore the need for further research in TA-TMA.